Risk Factors For Recurrence In Epilepsy Patients - Yudhisman Imran; Reza Naulla (CoinReads Media Prima, 2026)
Epilepsy is a chronic neurological disorder characterized by recurrent seizures resulting from abnormal electrical activity in the brain. It remains a significant global health concern, particularly in low- and middle-income countries (LMICs). The recurrence of seizures in patients with epilepsy is influenced by multiple clinical and nonclinical factors involved in epileptogenesis. This literature review aims to summarize the risk factors for recurrent seizures in patients with epilepsy based on recent scientific evidence. The literature was obtained from PubMed, Google Scholar, and manual searches and included articles published in English and Indonesian between 2010 and 2026. The study designs included meta-analyses, systematic reviews, cohort studies, case-control studies, cross-sectional studies, and case reports. The findings indicate that seizure recurrence is associated with the etiology of epilepsy (structural, genetic, infectious, metabolic, immunological, and idiopathic), as well as with lifestyle and behavioral factors such as sleep deprivation, psychological stress, alcohol consumption, smoking, and non-adherence to antiepileptic drugs. Abnormal MRI findings also increase the risk of disease recurrence. Furthermore, neuroinflammatory mechanisms, particularly microglial activation and proinflammatory cytokine release, contribute to increased neuronal excitability. In conclusion, recurrent seizures in epilepsy result from complex interactions among biological, clinical, and behavioral factors. Early identification and management of these risk factors are essential to reduce seizure recurrence and improve the quality of life of patients.